Administrasi Pendidikan: Tinjauan Teoritis tentang Ruang Lingkup dan Perannya dalam Mutu Pembelajaran - Muharromah, Fityatul; Fatimah, Meti (Lembaga Yasin AlSys, 2026)
Educational administration is a fundamental aspect that determines the effectiveness of educational provision, particularly in the systematic, planned, and sustainable management of various resources. This study aimed to describe the scope of educational administration through a comprehensive literature review. The method employed was library research by analyzing various academic references, government regulations, and research reports relevant to educational administration. The review findings show that the scope of educational administration encompasses several main domains, namely curriculum administration, student affairs administration, administration of educators and education personnel, administration of facilities and infrastructure, financial administration, public relations administration, and administration of special services. Each domain plays a strategic role in supporting the achievement of educational objectives through interrelated functions of planning, implementation, and evaluation. In addition, the study found that the main challenges in educational administration include limited resources, weak governance, insufficient human resource competence, and low levels of transparency and integration across administrative domains. This study concludes that professional, standardized, and integrated educational administration is urgently needed to improve the quality of education and to respond to the dynamic needs of education in the modern era.